2021
DOI: 10.1002/humu.24253
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of recessive diseases in the Vietnamese population from large‐scale clinical exome sequencing

Abstract: Accurate profiling of population‐specific recessive diseases is essential for the design of cost‐effective carrier screening programs. However, minority populations and ethnic groups, including Vietnamese, are still underrepresented in existing genetic studies. Here, we reported the first comprehensive study of recessive diseases in the Vietnamese population. Clinical exome sequencing data of 4503 disease‐associated genes obtained from a cohort of 985 Vietnamese individuals was analyzed to identify pathogenic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Our study showed that 4.6% of Vietnamese pregnant women identified as PAH carriers were asymptomatic at study enrollments. Our study figure was higher than the previously reported PAH frequency of 2.5% (or 1 in 40 individuals) in a cohort of 985 participants from the general population in Vietnam (Tran et al, 2021 ). This earlier publication included 985 participants spanning several age groups (fetuses, neonates, and adults) and both sexes (46% female and 54% male), whilst this study had 3259 pregnant women.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Our study showed that 4.6% of Vietnamese pregnant women identified as PAH carriers were asymptomatic at study enrollments. Our study figure was higher than the previously reported PAH frequency of 2.5% (or 1 in 40 individuals) in a cohort of 985 participants from the general population in Vietnam (Tran et al, 2021 ). This earlier publication included 985 participants spanning several age groups (fetuses, neonates, and adults) and both sexes (46% female and 54% male), whilst this study had 3259 pregnant women.…”
Section: Discussioncontrasting
confidence: 84%
“…However, all PAH variants in our study were heterozygous, and this finding is consistent with a previously reported heterozygous predominance (Blau et al, 2014;Hillert et al, 2020;Zschocke et al, 1995). The results from our study reveal that PKU carrier frequency was higher amongst the Vietnamese and other Eastern Asian populations, and it appears that PKU is underreported (Lazarin et al, 2012;Tran et al, 2021).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations